The Bow in the Borderland in the 16th Century - Aleksander Bołdyrew (Fasciculi Archaeologiae Historicae, 2017)
After finishing a long-term conflict with the State of the Teutonic Order (1521, 1525), the Polish foreign policy directed its focus to the East, which resulted in the necessity to reorganise the armed forces, at least partially. It translated, among other things, into changes in the military technology. The latter, in turn, had to be gradually adapted to the unique military culture which dominated in the Eastern and South-Eastern theatre of military operations. Among many symptoms of these changes, some can be observed in the area of weaponry. This was a natural process, observed also in other territorial and temporal contexts, which normally took place after two different war customs had met. In the 16th century Eastern and South-Eastern theatre of military operations, a perfect example is offered by the abandonment and later the return to using the bow and arrow in combat.